2004
DOI: 10.1002/gps.1194
|View full text |Cite
|
Sign up to set email alerts
|

Conversion pseudodementia in older people: a descriptive case series

Abstract: The author suggests that conversion pseudodementia in older people is caused by a catastrophic reaction to cumulative loss in later life in individuals who have predisposing borderline and narcissistic personality traits. Treatment using psychotherapeutic approaches may limit the progression of the syndrome if it is recognised at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…La richesse conceptuelle des neuropsychiatres germaniques est donc totalement oblitérée, d'autant plus que le Textbook of psychiatry du psychiatre suisse ne comporte aucune référence bibliographique. Par ailleurs, dans la lignée des travaux psychopathologiques sur la pseudodémence [39][40][41][42][43], la mise à jour des enseignements méconnus des maîtres allemands peut aider à réinterroger la dimension psychogène névrotique ou psychotique de la pseudodémence où le modèle d'une clinique de l'inhibition [44] possède toute sa pertinence. Enfin, tout comme d'autres prises de position contemporaines [45], cette démarche de questionnement invite à la prudence et la modération face aux volontés prédictives actuelles d'établir des diagnostics pré-démentiels [46].…”
Section: Resultsunclassified
“…La richesse conceptuelle des neuropsychiatres germaniques est donc totalement oblitérée, d'autant plus que le Textbook of psychiatry du psychiatre suisse ne comporte aucune référence bibliographique. Par ailleurs, dans la lignée des travaux psychopathologiques sur la pseudodémence [39][40][41][42][43], la mise à jour des enseignements méconnus des maîtres allemands peut aider à réinterroger la dimension psychogène névrotique ou psychotique de la pseudodémence où le modèle d'une clinique de l'inhibition [44] possède toute sa pertinence. Enfin, tout comme d'autres prises de position contemporaines [45], cette démarche de questionnement invite à la prudence et la modération face aux volontés prédictives actuelles d'établir des diagnostics pré-démentiels [46].…”
Section: Resultsunclassified
“…With regard to prognosis, there are differences between the reported cases. In some patients, there was significant improvement of cognitive function, whereas others lost their functionality and became dependent on their family, relatives or other caregivers 22,23 . Furthermore, the number of cases is small, so definite conclusions cannot be made at present.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…We used pseudodementia, conversion pseudodementia, hysterical pseudodementia, hysteria and conversion disorder as key words for our search. This review of the literature from 1961 to 2004 revealed only a few reported cases of pseudodementia as a conversion reaction 16,22–30 . In the case of old patients, the most complete recording has recently been published by Hepple 22 .…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, different to depressive pseudodementia that has been recognized to convert to dementia in up to 70% of cases, conversive pseudodementia courses with a syndrome that includes cognitive impairment, functional regression, and increasing physical dependency without evidence of organic deterioration [2,3].…”
Section: Introductionmentioning
confidence: 98%